Mobilités internationales et ressources en contexte métropolitain : trajectoires centraméricaines à Mexico - Laurent Faret (EchoGéo)
The article aims to document and analyze the forms of mobilization of resources for Central American migrants entering a new metropolitan environment, that of the urban area of ​​Mexico City. In an attempt to shed light on contemporary migration dynamics, where the situation of "frustrated trajectories" have become more evident as the routes become more complex, the article deals with the relationship between mobility trajectories and installation in the metropolitan area, as with the tensions between migratory resources and urban resources. Beyond transit processes, the short-term or more lasting presence of a mobile population from the Central America’s Northern Triangle (Salvador, Honduras and Guatemala) questions the forms of anchorage in the city and the socio-spatial relationships of these populations with the different urban and metropolitan dynamics. If the attractiveness of the urban area of ​​Mexico is real, migrant trajectories are also the result of blocked trajectories, either in an attempt to migrate to the North or due to impossible return to the country of origin. Between disrupted migratory projects and weakness of family and social networks, these populations construct adaptive strategies of settlement and socio-economic integration, building despite vulnerability a new horizon anchored locally.